Mwathirika sebagai Materi Tambahan dalam Mempelajari Sejarah 1965 - Tika Savitri (Universitas Gadjah Mada, 2019)
30th of September Movement, or Gerakan 30 September in 1965 was one of the watershed moments in the course of history of Indonesia. The transition to the New Order from the Old Order and the events surrounding it are deemed so important that the Department of Education and Culture includes it into the official curriculum taught at XII grade students. G30S and the conflicts around the year 1965 are pictured in an optimistic tint, like a good struggle towards a better new era of development. On the other hand, what happened – and what is felt - in the artistic world is more on the contrary, since many artists associate the events with dark, dreadful situations of violence and unrest. Mwathirika by Papermoon Puppet Theater is one example of artists’ works regarding G30S, with this one in particular using the medium of contemporary puppet theater. The play Mwathirika itself doesn’t explicitly show the transition of governmental power. Instead, it focuses on the loss of the victims around the events. These differing point of views from the government and artistic world is what prompted this research, thus arriving to the question of whether contemporary performance art can provide supplemental education for high school students, especially regarding sensitive matters in one own’s history.